Imagining Virginia Woolf : An Experiment in Critical Biography - DiBattista, Maria, 1947- (Book collections on Project MUSE., 2009)
Where other works of literary criticism are absorbed with the question--How to read a book?--Imagining Virginia Woolf asks a slightly different but more intriguing one: how does one read an author? Maria DiBattista answers this by undertaking an experiment in critical biography. The subject of this work is not Virginia Woolf, the person who wrote the novels, criticism, letters, and famous diary, but a different being altogether, someone or something Maria DiBattista identifies as "the figment of the author." This is the Virginia Woolf who lives intermittently in the pages of her writings and i.